2017
DOI: 10.1007/s00382-017-3548-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of sea-ice albedo in the climate of slowly rotating aquaplanets

Abstract: We investigate the influence of the rotation period (Prot) on the mean climate of an aquaplanet, with a focus on the role of sea-ice albedo. We perform aquaplanet simulations with the atmospheric general circulation model ECHAM6 for various rotation periods from one Earth-day to 365 Earth-days in which case the planet is synchronously rotating. The global-mean surface temperature decreases with increasing Prot and sea ice expands equatorwards. The cooling of the mean climate with increasing Prot is caused part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…It is important to note that diurnal cycle effects are neglected, and although they might become important for short orbital periods, they are out of the scope of this study. Salameh et al (2018) showed that diurnal effects on the surface temperature become important when the ratio between the orbital period (ω) and the rotation period (P Ω ) is ω/P Ω ≈ 10. In this case, ω/P Ω = 45, so neglecting diurnal effects is justified.…”
Section: Surface Temperature Responsementioning
confidence: 99%
“…It is important to note that diurnal cycle effects are neglected, and although they might become important for short orbital periods, they are out of the scope of this study. Salameh et al (2018) showed that diurnal effects on the surface temperature become important when the ratio between the orbital period (ω) and the rotation period (P Ω ) is ω/P Ω ≈ 10. In this case, ω/P Ω = 45, so neglecting diurnal effects is justified.…”
Section: Surface Temperature Responsementioning
confidence: 99%
“…Second, it shows that if the top-of-atmosphere ice/ocean albedo contrast is smaller, a planet is less likely to experience a snowball bifurcation (C * increases). This is important because tidally locked terrestrial planets should have massive cloud decks on their day sides (Yang et al 2013;Way et al 2015;Kopparapu et al 2016;Salameh et al 2017). This should tend to increase the top-ofatmosphere albedo over open ocean regions, making the effective albedo contrast between ocean and ice/snow smaller.…”
Section: Tidally Locked Planetmentioning
confidence: 99%
“…It is also useful in determining the occurrence of potentially habitable planets in our galaxy, as was done with Kepler data. Several groups have studied the limits of the mainsequence HZ (Kasting et al 1993;Pierrehumbert & Gaidos 2011;Kopparapu et al 2013;Leconte et al 2013a;Yang et al 2013;Barnes et al 2013;Zsom et al 2013;Kopparapu et al 2014;Wolf & Toon 2014;Yang et al 2014a;Way et al 2015;Wolf & Toon 2015;Leconte et al 2015;Godolt et al 2015;Kopparapu et al 2016;Haqq-Misra et al 2016;Ramirez & Kaltenegger 2017;Salameh et al 2017) using both 1-D and 3-D climate models, and corresponding climate transitions that planets undergo at these limits. Many of these models assume water-rich (∼ 1 Earth ocean) planets, which is reasonable if one wants to study the surface habitability of a planet.…”
Section: Introductionmentioning
confidence: 99%